Drawing as a tool of thought and construction: architecture through the archive of Paride Pozzi - Giovanni Rasetti (Disegnare con)
This study highlights the importance of research on architectural archives and, in particular, on those relating to lesser-known provincial designers. One such archive is that of Paride Pozzi, which testifies to the central role of drawing in the design and construction process. Encompassing an extensive collection of sketches, technical drawings, notes, and correspondence, the as-yet unpublished corpus—declared of historical interest in 2001—remains to be classified and reveals that drawing for this designer served as more than merely a representational medium, functioning instead as a true instrument of thought, analysis, and communication. The proposed research, based on the analysis of archival materials through graphic representation, aims to integrate both a graphic and a historical-critical analysis of the drawings with three-dimensional reconstruction techniques, in order to document the design phases and preserve the cultural identity. The Architect Paride Pozzi (1895-1981) was born in Rivarolo Mantovano, from 1919 to 1922, he studied at the Regio Istituto di Belle Arti di Parma, where he graduated from the Special Architecture Course and became a professor of Architectural Drawing. In 1937 he settled in Pescara, in the Abruzzo region, where in the post-war period he made a significant contribution to the local architectural scene. The drawings in the archive range from pencil sketches to detailed ink plates on tracing paper, reflecting a sustained and in-depth practice of drawing as a means of exploring architectural ideas. Pozzi used multiple hypotheses and explored formal possibilities on paper to bring his ideas into focus. This approach embodies a compositional methodology typical of twentieth-century professionals, in which the selective process of multiple variations becomes fundamental in deciding which design hypothesis to develop. DOI: https://doi.org/10.20365/disegnarecon.34.2025.22